Menstrual and reproductive factors in women, genetic variation in CYP17A1, and pancreatic cancer risk in the European prospective investigation into cancer and nutrition (EPIC) cohort. - Duell, E; Travier, N; Lujan-Barroso, L; Dossus, L; Boutron-Ruault, M; Clavel-Chapelon, F; Tumino, R; Masala, G; Krogh, V; Panico, S; Ricceri, F; Redondo, M; et al. (2013)
Menstrual and reproductive factors and exogenous hormone use have been investigated as pancreatic cancer risk factors in case-control and cohort studies, but results have been inconsistent. We conducted a prospective examination of menstrual and reproductive factors, exogenous hormone use and pancreatic cancer risk (based on 304 cases) in 328,610 women from the EPIC cohort. Then, in a case-control study nested within the EPIC cohort, we examined 12 single nucleotide polymorphisms (SNPs) in CYP17A1 (an essential gene in sex steroid metabolism) for association with pancreatic cancer in women and men (324 cases and 353 controls). Of all factors analyzed, only younger age at menarche (<12 vs. 13 years) was moderately associated with an increased risk of pancreatic cancer in the full cohort; however, this result was marginally significant (HR = 1.44; 95% CI = 0.99-2.10). CYP17A1 rs619824 was associated with HRT use (p value = 0.037) in control women; however, none of the SNPs alone, in combination, or as haplotypes were associated with pancreatic cancer risk. In conclusion, with the possible exception of an early age of menarche, none of the menstrual and reproductive factors, and none of the 12 common genetic variants we evaluated at the CYP17A1 locus makes a substantial contribution to pancreatic cancer susceptibility in the EPIC cohort.